Teacher Strategies in Character Formation to Enhance Students’ Social Attitudes at Madrasah - K, Mirzat; Misnah, Misnah; Hasan, Hasan (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study investigates the strategies teachers employ to shape students’ character and enhance social attitudes at Tsanawiyah Alkhairaat Madrasahs in Ampibabo District. The background of this research lies in the urgency of character education in developing students who are not only intellectually capable but also socially responsible and morally grounded. The study aims to describe in depth how teachers plan, implement, and evaluate learning processes that integrate moral and social values through Social Studies (IPS) instruction. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation at MTs Alkhairaat Ampibabo and MTs Alkhairaat Sidole. The findings reveal that teachers’ strategies effectively foster students’ social attitudes when they combine interactive methods, moral modeling, and school culture. At MTs Alkhairaat Ampibabo, teachers apply group discussions, collaborative projects, and social activities to strengthen empathy, cooperation, and responsibility. Meanwhile, teachers at MTs Alkhairaat Sidole emphasize exemplary behavior and positive routines rooted in religious and disciplinary values. The results indicate a significant improvement in students’ social behaviors, such as mutual respect, cooperation, and social responsibility. The study concludes that successful character formation requires consistency among classroom learning, school environment, and family involvement. The implication of this research highlights the importance of integrating character education strategies into every aspect of teaching practice to cultivate socially aware and morally upright students.